Toward the Existence of a Sympathetic Neuroplasticity Adaptive Mechanism Influencing the Immune Response. A Hypothetical View—Part I - Bottasso, Emanuel (Frontiers in Endocrinology, 2019)
The nervous system exerts a profound influence on the function of the immune system (IS), mainly through the sympathetic arm of the autonomic nervous system. In fact, the sympathetic nervous system richly innervates secondary lymphoid organs (SLOs) such as the spleen and lymph nodes. For decades, different research groups working in the field have consistently reported changes in the sympathetic innervation of the SLOs during the activation of the IS, characterized by a decreased noradrenergic activity and retraction of these fibers. Most groups interpreted these changes as a pathological phenomenon, referring to as “damage” or “injury” of the noradrenergic fibers. Some of them postulated, that this “injury” was probably due to toxic effects of released endogenous mediators. Others, working in animal models of chronic stimulation of the IS, linked it to the very chronic nature of processes. Unlike these views, this first part of the present work reviews evidence supporting the hypothesis on the existence of a specific adaptive mechanism of neural plasticity from sympathetic fibers innervating SLOs, encompassing structural and functional changes of noradrenergic terminals. This plasticity program would involve segmental retraction and degeneration of these fibers during the activation of the IS with subsequent regeneration once the steady state is recovered. The candidate molecules likely to mediate this phenomenon are also here introduced. The second part will extend this view as to the potential changes in sympathetic innervation likely to occur in inflamed non-lymphoid peripheral tissues and its possible immunological implications.